How Tight Is Too Tight? : A Look at Welfare Implications of Distortionary Policies in Uzbekistan - Grigorian, David (IMF Working Papers; Working Paper ;, 2005)
Since independence in 1991, Uzbekistan has pursued a gradual approach to the transition from planned to market economy. This approach relied heavily on trade controls, directed credit, and large public investments. A number of financial sector measures were also instituted that distorted resource allocation and increased transaction costs. As a result, while possibly preventing the contraction of output in the early 1990s, these policies led to disappointing economic outcomes and social conditions. The paper reviews the underlying distortions and presents survey-based evidence to support their existence and their detrimental impact on economic activity. Looking forward, the paper-using a representative agent framework to model existing financial sector distortions-offers some guidance regarding the likely implications of eliminating the observed distortions on key aggregate variables. It suggests that the elimination of these distortions will enhance welfare and lead to increased investment and capital stock.